Transformasi Kementerian Hukum dan Hak Asasi Manusia Jawa Barat dalam Pelayanan di Masa Pandemi: Studi Kasus Proses Transformasi Website Oleh Humas Kemenkumham Jawa Barat dalam Pelayanan di Masa Pandemi - Khairunisa Shafira Firdaus; Ani Yuningsih (UNISBA Press, 2023)
Abstract. Publication and management of information is the main responsibility of public relations practitioners in all situations, especially during the Covid-19 pandemic. Therefore, the Public Relations of the West Java Ministry of Law and Human Rights Regional Office (Kanwil Kemenkumham Jabar) changed services from manual to automatic and digital-based through the transformation of the official website. This digital service transformation process becomes the task of Public Relations in the Bureaucratic Reform and Information Technology subsection to facilitate information and services during the Covid-19 pandemic. The research